(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Metformin, taken by nearly 120 million people across the world as a treatment for type 2 diabetes, has a relatively short plasma half-life and low absolute bioavailability. In this study, physicochemical and pharmacokinetics properties of metformin have been thoroughly assayed using ADMETLab, SwissADME, SmartCYP, LigandScout web-servers and software to evaluate the effectiveness of its formulation as controlledrelease matrix tablets. The objective of the present work was to develop a formulation of an oral controlled-release (CR) metformin tablet, using hydrophilic hydroxylpropylmethylcellulose (HPMC) grades K4M and K100M polymers at different concentrations utilizing computational simulatory tools. Intestinal membrane permeability of the drug has been assayed using 2 hours simulation run with MembranePlus Software. Simulated environment generated for in silico dissolution study, using DDDPlus software, of the prepared formulations used USP Apparatus Type 2 rotating at 100 rpm. The simulation run was for 2 hours using 0.1N HCl phase followed by 8 hours with 6.8 USP Phosphate buffer phase. The results showed that drug release from the higher viscosity grade, K100M was slower as compared to the lower viscosity grade K4M at a fixed polymer concentration level. Furthermore, plasma concentration-time curves for the formulations have been generated using GastroPlus software. Dhaka Univ. J. Pharm. Sci. 22(1): 29-42, 2023 (June)